Nucleoside/nucleotide reverse transcriptase inhibitors attenuate angiogenesis and lymphangiogenesis by impairing receptor tyrosine kinases signalling in endothelial cells. (25th October 2017) - Song, Lin; Ding, Sha; Ge, Zhen; Zhu, Xiaolong; Qiu, Cong; Wang, Yuewen; Lai, Enyin; Yang, Weijun; Sun, Yi; Chow, Samson A; Yu, Luyang
Abstract : Background and Purpose: Cardiovascular disease associated with antiretroviral therapy (ART) has become a major clinical challenge for HIV‐positive patients. However, the role of ART in blood vessel growth is largely unknown. Here, we examined an integral component of ART, nucleoside/nucleotide reverse transcriptase inhibitors (NRTIs) and investigated their effects on key microvascular functions, including angiogenesis and lymphangiogenesis. Experimental Approach: The angiogenesis/lymphangiogenesis capability of endothelial cells (ECs) was evaluated using migration, proliferation and tube formation assays in vitro, and mouse ear and Matrigel plug assays in vivo . Expressions of signalling molecules and mitochondrial antioxidant catalases were determined using Western blotting. Receptor tyrosine kinase (RTK) internalization and endocytosis were examined using flow cytometry and confocal immunofluorescence microscopy respectively. Mitochondrial DNA copy number and ROS were determined using quantitative real‐time PCR and MitoSOX staining respectively. Key Results: Pharmaceutical doses of NRTIs [azidothymidine (AZT), tenofovir disoproxil fumarate (TDF) and lamivudine (3TC)] inhibited angiogenesis and lymphangiogenesis both in vivo and in vitro by affecting the proliferation and migration of ECs. Correspondingly, NRTIs selectively attenuated the activation and transduction of endothelial RTK signals, VEGFR2 and FGFR1 pathways, in vascular ECs and the VEGFR3 pathway in lymphatic ECs. Both TDF and 3TC restrained RTKs' endocytosis into early endosomes but not internalization, while AZT blocked the protein maturation of RTKs. Excessive ROS levels were detected in NRTI‐treated ECs, and the MnSOD mimic MnTMPyP alleviated the angiogenic/lymphangiogenic defects induced by NRTIs. Conclusions and Implications: NRTIs negatively regulate angiogenesis and lymphangiogenesis by inducing mitochondrial oxidative stress and subsequently impairing RTK signalling in ECs. Linked Articles: This article is part of a themed section on Spotlight on Small Molecules in Cardiovascular Diseases. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v175.8/issuetoc